Influence of different types of plant extracts on the Streptococcus sobrinus culture - V. Klitynska, Oksana; Y. Kostenko, Yeugen; R. Gurando, Viacheslav; M. Karpinets, Victoria (Journal of Stomatology, 2016)
Introduction. Microbiological status of children and adolescents with the establishment of the prevalence of certain kinds of microorganisms is the etiological factor of occurrence and progression of various dental diseases. Aim of the study. To determine the effect of different types of plant extracts on the culture of Streptococcus sobrinus. Materials and methods. The study examined the effect of plant extracts on the culture of Streptococcus sobrinus, cultured in the oral cavity fluid in 146 children aged 3-8 years of different ethnic groups with varying degree of caries who resided permanently in biogeochemical conditions with shortage of fluoride and iodine. Results. Absence of growth of Str. sobrinus when exposed to cranberry, red currant, cherry and jostaberry extracts was demonstrated. Several dilutions of extracts were studied. No microorganism growth when exposed to the plum extract in dilutions of 1:1 and 1:2, 1:8, 1:16 was observed; in dilutions of 1:4 and 1:6 significant growth inhibition was reported when compared to controls (1±0.15×102, 1±0.1×102; 0; p<0.05). Conclusions. The most effective plant extracts against Str. Sobrinus are extracts of cranberry, redcurrant, cherry and jostaberry in that they can be recommended in your diet in comprehensive prevention of dental caries in children as no effective means of endogenous drug prevention in preschool and primary school age has so far been introduced.